MR-Imaging of teeth and periodontal apparatus: an experimental study comparing high-resolution MRI with MDCT and CBCT - Gaudino, Chiara; Cosgarea, Raluca; Heiland, Sabine; Csernus, Reka; Beomonte Zobel, Bruno; Pham, Mirko; Kim, Ti-Sun; Bendszus, Martin; Rohde, Stefan (European radiology, 2011)
The aim of this study was (1) to assess the ability of magnetic resonance imaging (MRI) to visualize dental and periodontal structures and (2) to compare findings with multidetector computed tomography (MDCT) and cone beam CT (CBCT).
Gesehen am 09.08.2023